Molecular structure of deoxycytidyl-3'-methylphosphonate (RP) 5'-deoxyguanidine, d[Cp(CH3)G]. A neutral dinucleotide with Watson-Crick base pairing and a right handed helical twist. - Han, F (1990)
The crystal structure of d[Cp(CH3)G] has been determined as part of a project to study the mechanism of the B----Z transition in DNA. The asymmetric unit contains two dinucleotides and the equivalent of 7.5 water molecules, partially disordered over 12 definable positions. The two symmetry-independent dinucleotides form a duplex with Watson-Crick base-pairing and a right-handed helical sense. Comparison with previously determined structures of the B and A conformation showed that this duplex is closer to B than to A but significantly different from B. It corresponds to a stretched out helix with a 4 A rise per base pair and a helical twist of 32 degrees. This structure may serve as a model for the bending of DNA in certain situations. The configuration at the methyl phosphonate is RP, and a mechanism, based on this assignment, is presented for the B----Z transition in DNA.